Hearing loss on social media: Who is winning hearts and minds?. (8th October 2017) - Crowson, Matthew G.; Tucci, Debara L.; Kaylie, David
Abstract : Objectives/Hypothesis: To analyze specific patterns of Twitter usage using common references to hearing loss, and characterize the virtual public that comprises the hearing loss community to inform hearing loss stakeholders for opportunities for engagement and outreach. Study Design: Social media network analysis. Methods: Twitter tweets were sampled from July 2016 to September 2016 using #hearing, #hearingloss, #deaf, #hearingimpairment, #hardofhearing, #deafness, #hearingmatters, #hearinghealth, and #hearingimpaired tags. User and Twitter social community metrics were examined including temporal trends, tweet content, user activity, tweet reach, and an analysis of the tweets' social network. Results: We identified and analyzed 49, 208 tweets from July 2016 to September 2016 with tags relevant to hearing loss. Of the 100 most active Twitter accounts, organizations owned 67% compared to 33% owned by individuals. Commercial/for profit and informational organizations were the most common organization account owners (26% and 16%, respectively). Five unique tweets were identified as each having a reach of over 100, 000 Twitter users, with the greatest reach exceeding 250, 000 users. Temporal analysis identified marked retweet outliers (>300 retweets per hour) that corresponded with a widely publicized event involving the dismissal of a deaf employee from a fast‐food chain store. Conclusions: Twitter accounts owned by organizations outnumbered individual accounts, and commercial/for profit user accounts were the most frequently active organization account type. Tweets pertaining to hearing loss may have a broad reach to a large community base. Analyses of social media use can be helpful in discovering issues of interest to the hearing loss community, as well as determining which users and organizations are dominating social network conversations. Level of Evidence: NA. Laryngoscope, 128:1453–1461, 2018